Priorities of local OTT platforms' internationalization strategies - Jinyoung Nam; Yoonhyuk Jung (International Telecommunications Society (ITS), 2024)
Digitalization is widely recognized as a pivotal force influencing the evolution of the business world and societies at large (Cortellazzo et al., 2019). Media platforms have entered foreign markets to grab new opportunities, especially for geographic and product expansion in the global market. Over-the-top (OTT) platforms focus on global expansion into diverse regions, aiming for platform expansion in the global market. Many established competitors have led to many OTT platforms including Netflix expanding internationally (Deloitte, 2018). For instance, Paramount planned to commission 150 original international programs for Paramount Plus streaming services by 2025, while Disney Plus has expanded its services in the international regions (FICDC, 2022). OTT platforms have become the main distribution and consumption channel for digital content by global users.
Keywords: 330; Over-the-top (OTT) platforms; Internationalization strategies; AHP analysis